The Organizational Context of Substantiation in Child Protective Services Cases - Font, Sarah (Journal of interpersonal violence, 2021)
Substantiation of child maltreatment is among the most important decisions made by Child Protective Services and may have wide-reaching implications for child and family well-being. Yet, relatively little research has been undertaken to understand the organizational context of substantiation. Using national population data from the United States, this study examined the associations between state and county contexts with county substantiation rates using multilevel negative binomial regression. The results show that organizational context (policy and practice characteristics) influences substantiation rates. In particular, standards of evidence, alternative options for investigation and disposition of allegations, and workload burden were all significant predictions of substantiation rates. However, the associations of organizational factors and substantiation varied across types of maltreatment allegations; neglect and physical abuse allegations were more heavily influenced by organizational factors than sexual abuse or multi-type maltreatment allegations. Implications for child protection policy and practice are discussed.